- عبد الرزاق نجيبة - سوريا في عهد حكم حافظ الأسد (1970-2000م) (جامعة محمد بوضياف بالمسيلة, 2025)
تتناول هذه الدراسة تاريخ سوريا في عهد الرئيس حافظ الأسد (1970-2000)، مسلطة الضوء على التحولات السياسية والاقتصادية والاجتماعية العميقة التي شهدتها البلاد خلال ثلاثة عقود من حكمه.تبدأ الدراسة بتحليل الخلفية التاريخية لسوريا منذ الاستقلال عام 1946، مرورًا بسلسلة الانقلابات العسكرية (1949-1954)، وتجربة الوحدة مع مصر (1958-1961)، وصولاً إلى صعود حزب البعث وانقساماته الداخلية التي مهدت لوصول الأسد إلى السلطة عبر "الحركة التصحيحية" في تشرين الثاني/نوفمبر 1970.تحلل الدراسة بنية النظام السياسي الذي أسسه الأسد، والذي ارتكز على ثلاثية: الحزب-الجيش-الأجهزة الأمنية، مع تكريس دستور 1973 لصلاحيات شبه مطلقة للرئيس وهيمنة حزب البعث على مؤسسات الدولة والمجتمع. كما تبحث في سياسات القمع الممنهج للمعارضة، سواء اليسارية أو الإسلامية، والتي بلغت ذروتها في أحداث حماة 1982.على الصعيد الخارجي، تتناول الدراسة العلاقات الاستراتيجية مع الاتحاد السوفيتي، ودور سوريا في حرب 1973، والتدخل في لبنان، والعلاقات المعقدة مع دول الجوار، وصولاً إلى المشاركة في مفاوضات السلام في التسعينيات.اقتصاديًا واجتماعيًا، ترصد الدراسة التحول من السياسات الاشتراكية في السبعينيات، مرورًا بأزمات الثمانينيات، وصولاً إلى الانفتاح المحدود في التسعينيات عبر قانون الاستثمار رقم 10. كما تحلل التحولات الاجتماعية، بما فيها صعود الطبقة الوسطى البيروقراطية، والتعامل مع التنوع الطائفي والإثني، ووضع المرأة والأقليات.تختتم الدراسة بتحليل مشروع التوريث السياسي في التسعينيات، والذي تُوّج بانتقال السلطة إلى بشار الأسد عام 2000، محولاً سوريا إلى نموذج "الجمهوركية" - أي الجمهورية ذات الطابع الوراثي.تكشف الدراسة أن عهد حافظ الأسد، رغم تحقيقه للاستقرار السياسي النسبي وتعزيز دور سوريا الإقليمي، جاء على حساب الحريات السياسية والتنمية المستدامة والعدالة الاجتماعية، منتجًا دولة أمنية سلطوية تحمل في داخلها بذور أزماتها المستقبلية This study examines the history of Syria during the era of President Hafez al-Assad (1970-2000), highlighting the profound political, economic, and social transformations that the country witnessed during three decades of his rule.The study begins by analyzing Syria's historical background since independence in 1946, through the series of military coups (1949-1954), the unity experience with Egypt (1958-1961), and the rise of the Ba'ath Party and its internal divisions that paved the way for Assad's ascension to power through the "Corrective Movement" in November 1970.The study analyzes the political system structure established by Assad, which was based on the trinity of: Party-Army-Security Apparatus, with the 1973 constitution enshrining near-absolute powers for the president and Ba'ath Party dominance over state and society institutions. It also examines the systematic repression policies against opposition, whether leftist or Islamist, which reached their peak in the Hama events of 1982.On the foreign front, the study addresses strategic relations with the Soviet Union, Syria's role in the 1973 war, intervention in Lebanon, complex relations with neighboring countries, and participation in peace negotiations in the 1990s.Economically and socially, the study traces the transformation from socialist policies in the 1970s, through the crises of the 1980s, to the limited opening in the 1990s through Investment Law No. 10. It also analyzes social transformations, including the rise of the bureaucratic middle class, dealing with sectarian and ethnic diversity, and the status of women and minorities.The study concludes by analyzing the political succession project in the 1990s, which culminated in the transfer of power to Bashar al-Assad in 2000, transforming Syria into a model of "republarchy" - a republic with hereditary characteristics.The study reveals that Hafez al-Assad's era, despite achieving relative political stability and enhancing Syria's regional role, came at the expense of political freedoms, sustainable development, and social justice, producing an authoritarian security state that carried within it the seeds of its future crises